Angst of displacement in V.S. Naipaul’s Magic Seeds (Journal of Innovation in Academia, 2025)
This paper aims to explore how Naipaul articulates dislocated and disjointed sensibility of the individuals drifting in diasporic location. Presenting precarious situatedness between ancestral and adopted homeland, Willy, the anti-hero of Magic Seeds, represents the problems of post-coloniality such as difficulties in discovering roots, detecting one’s own history and finding an authentic identity. By taking theoretical insights on diaspora identity and hegemonic relationships in identity formation, this paper reveals that Naipaul snubs diasporic space regarding it to be a threshold to estrangement and alienation.